Why Villagers Use Toilets Only During Specific Time and Season? A Mixed-Methods Study in Rural Tamil Nadu - Nancy S; K Mujibur Rahman; K Mohamed Ali; Govindarajan PK; Thirumeni S (Medsci Publications, 2022)
Background: Due to the efforts of sanitation promotion interventions in India, majority of the villagers started using toilets. But there is an inconsistency in toilet usage with regard to time and season. Objectives: The objectives were to determine the time and seasonal variations in toilet usage among villagers who use toilets and to identify the reasons for time and seasonal variations in toilet usage. Methodology: A community-based mixed-methods study was executed in the four field practice villages of UHTC, Villupuram. After IEC clearance, 405 individuals who were using an owned toilet were selected by Simple Random Sampling. Qualitative component (free listing) was used for questionnaire development and quantitative component (survey + observation) was used for data collection. Results: Majority, 52% villagers used toilets only in the night and 64% villagers used toilets during rainy season. Fear of darkness and snakes, emergency and large family size were the common reasons for night time toilet usage. While, non-availability of open space, illness on exposure to rain and quick filling of toilet pit contributed to toilet usage in the rainy season. Conclusion: The study findings would help in the development of culturally-sensitive and socially-acceptable key messages for future sanitation promotion interventions.